Pengembangan Kecerdasan Spiritual Anak Sekolah Dasar - Komang Satya Permadi; Putu Yulia Angga Dewi; Ketut Bali Sastrawan; Kadek Hengki Primayana (Edukasi: Jurnal Pendidikan Dasar, 2020)
This research is a qualitative research. The data obtained through the interview process. The results showed that the objective of education aims to provide values and norms to an individual that will guide his behavior. However, nowadays children and adolescents are facing a problem that is called spirituality crisis. We regularly see crimes committed by them, such as; robbery, gambling, brawls between schools, murder, drug addiction and others. This is due to inexistence of balance between religiousity values in the individual itself and with the future progress that moving forward continuously. The higher IQ that people have, the more they will experts in intellectual fields, likewise EQ. It has important role in building effective human relationships. Meanwhile, SQ serves to transform spiritual values such as honesty, compassion, justice, honesty, responsibility, peace, trust and togetherness. Keywords: Spiritual Intelligence and Emotional Intelligence